2000
DOI: 10.1016/s0008-6363(99)00319-3
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular reflex responses induced by epicardial chemoreceptor stimulation

Abstract: The cardiac mechano- and chemoreceptors are broadly distributed in the myocardium and coronary vessels. A portion of these receptors extends over the epicardium and pericardium and therefore can be excited by mechanical or chemical stimuli directly applied to the surface of the heart. Excitation of epicardial receptors by topical application of chemical compounds elicits a variety of reflex cardiovascular responses, without the vascular or systemic effects of the drug administered systemically. A considerable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 99 publications
0
6
0
Order By: Relevance
“…Stable hemodynamic forces are needed to preserve normal ventricular dimensions and functional parameters, and to avoid heart adaptation [114] . The pericardium fulfills an important role in stabilizing several mechanical parameters: it limits heart dilatation during diastole, reduces endomyocardial tension, prevents cardiac hypertrophy in pressure overload conditions, prevents ventricular-atrial blood retrogression under high end-diastolic ventricular pressure, preserves negative endothoracic pressure (crucial for atrial blood filling) and regulates cardiac frequency and arterial blood pressure [27] , [42] , [51] . In the adult, physiological levels of wall shear stress suppress proliferation of endothelial cells and promote their quiescence [112] .…”
Section: From Development To Homeostasis Disease and Regeneration: Mmentioning
confidence: 99%
“…Stable hemodynamic forces are needed to preserve normal ventricular dimensions and functional parameters, and to avoid heart adaptation [114] . The pericardium fulfills an important role in stabilizing several mechanical parameters: it limits heart dilatation during diastole, reduces endomyocardial tension, prevents cardiac hypertrophy in pressure overload conditions, prevents ventricular-atrial blood retrogression under high end-diastolic ventricular pressure, preserves negative endothoracic pressure (crucial for atrial blood filling) and regulates cardiac frequency and arterial blood pressure [27] , [42] , [51] . In the adult, physiological levels of wall shear stress suppress proliferation of endothelial cells and promote their quiescence [112] .…”
Section: From Development To Homeostasis Disease and Regeneration: Mmentioning
confidence: 99%
“…The normal pericardium contributes in important functions. In is necessary for: (1) lubricating the moving surfaces of the heart, (2) stabilizing the heart anatomic position, (3) isolating the heart from the adjacent anatomical structures, prohibiting the adhesion formation, the inflammatory or neoplastic extention, (4) limiting heart dilatation during diastole, reducing the endomyocardial tension, (5) preventing cardiac hypertrophy in pressure overload conditions, (6) reducing the right ventricular impulse work in left ventricular overload conditions, (7) the ventriculoatrial blood retrogression prevention during high end-diastolic ventricular pressures, (8) the preservation of the negative endothoracic pressure, which is crucial for the atria blood filling, (9) the nervous stimulation response and regulation of the cardiac frequency and arterial blood pressure, (10) the formation of a hydrostatic compensation system ensuring that end-diastolic pressure remains the same at all hydrostatic levels and the Frank–Starling mechanism is functional (Holt, 1970 ; Goto and LeWinter, 1990 ; Cinca and Rodriguez-Sinovas, 2000 ).…”
Section: Physiologymentioning
confidence: 99%
“…Sensory nerve endings may act as potential sensor machinery for ischaemia, as ischaemia, hypoxia, lactate, K + and low pH were shown to stimulate cardiac sensory nerves in association with a release of their transmitters ( Franco‐Cereceda, 1988 ). Sensory nerves may exert a strong influence on cardiac function, cardiac reflexes and adaptive responses due to their nitric oxide (NO) and vasoactive peptide content, such as calcitonin gene‐related peptide and substance P ( Franco‐Cereceda, 1988 ; Ren and Ruda, 1995 ; Sosunov et al , 1995 , 1996 ; Cinca and Rodriguez‐Sinovas, 2000 ). In agreement with the hypotheses outlined above, through the use of capsaicin, we and others have previously shown that cardiac sensory nerves play a role in cardiac adaptation to ischaemic stress ( Li et al , 1996 ; Ferdinandy et al , 1997 ; Wang and Wang, 2005 ; Zhong and Wang, 2007 ), in the regulation of cardiac NO–cGMP system ( Csont et al , 2003 ) and in the mechanism of doxorubicin‐induced heart failure ( Katona et al , 2004 ).…”
Section: Introductionmentioning
confidence: 99%